2013
DOI: 10.1016/j.jmoldx.2013.05.008
|View full text |Cite
|
Sign up to set email alerts
|

miRNA Profiling Identifies Candidate miRNAs for Bladder Cancer Diagnosis and Clinical Outcome

Abstract: Bladder cancer is a common cancer in the Western world. The current prognosticators such as tumor grade, stage, size, and multifocality do not accurately reflect the clinical outcome. It is of clinical interest to identify biomarkers that could improve diagnostic and/or prognostic predictions. The objectives of this study were to identify deregulated miRNAs in bladder cancer samples and evaluate their potential as diagnostic and prognostic biomarkers. We screened 723 miRNAs by microarray and selected a subset … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
111
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 132 publications
(120 citation statements)
references
References 47 publications
6
111
1
Order By: Relevance
“…Studies show that miR-9, miR-182, and miR200b appear to be related to MIBC tumor aggressiveness and recurrence-free and overall survival. 5,11 Ratert et al 5 observed a correlation between miR-141 and miR-205 expression levels with the overall survival of the patients. Other studies revealed that some miRNAs, particularly miR-126, miR-182, and miR-199a could be found in larger quantities in the urine of bladder cancer patients than in the urine of controls, either healthy subjects or patients with infections.…”
Section: Mirna As Biomarkers For Diagnostics and Prognostication In Bmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies show that miR-9, miR-182, and miR200b appear to be related to MIBC tumor aggressiveness and recurrence-free and overall survival. 5,11 Ratert et al 5 observed a correlation between miR-141 and miR-205 expression levels with the overall survival of the patients. Other studies revealed that some miRNAs, particularly miR-126, miR-182, and miR-199a could be found in larger quantities in the urine of bladder cancer patients than in the urine of controls, either healthy subjects or patients with infections.…”
Section: Mirna As Biomarkers For Diagnostics and Prognostication In Bmentioning
confidence: 99%
“…16 Despite the limitations caused by the low number of participants, this proofof-concept study provides preliminary data that suggest the practicality of this method for the early detection of bladder cancer. A screening study performed by Ratert et al, 5 using microarray technology followed by a validation step using quantitative reverse transcription polymerase chain reaction (qRT-PCR), reveals a specific miRNA signature containing 15 miRNAs, of which seven (miR-100, miR-125b, miR130a, miR-139-5p, miR-145*, miR-199a-3p, miR-214, and miR-222) were upregulated and eight were downregulated 5 in tumor tissue versus healthy tissue. Furthermore, miR20a, miR-106b, miR-141, and miR-205 were found to be upregulated in bladder cancer, 17,18 in contrast to an inverse expression behavior in other locations such as renal or prostate cancer.…”
Section: -9mentioning
confidence: 99%
See 2 more Smart Citations
“…Using deep-sequencing analysis, we found that miR-141-3p expression was decreased by 1.26-fold in early PCa compared to that in BPH (P < 0.05), and confirmed a similar 1.17-fold decrease in early PCa compared to that in BPH (P = 0.2053) by qRT-PCR. In addition, miR-141-3p expression levels vary in different tumors, with overexpression observed in bladder [16], urothelial [17], breast [18] [19], ovarian [20], endometrioid [21], cholangiocytes [22] and colorectal cancers [23] and NSCLC [24], while expression is downregulated in gastric cancer [25], hepatocellular carcinomas [26] [27], renal cell carcinoma [28], lymphatic metastatic pancreatic cancer [29], pituitary tumors [30], craniopharyngioma [31], head and neck cancer [32], osteosarcoma [33], and cutaneous T cell lymphoma [34]. These reports provide compelling evidence for a role of miR-141-3p as an oncogene or tumor suppressor in different tumors and at different stages.…”
Section: Discussionmentioning
confidence: 99%